2020
DOI: 10.1007/s11096-020-01031-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and drug therapies in patients with the common-type coronavirus disease 2019 in Hunan, China

Abstract: Background Clinical characteristics of patients with the coronavirus disease 2019 (COVID-19) may present differently within and outside the epicenter of Wuhan, China. More clinical investigations are needed. Objective The study was aimed to describe the clinical characteristics, laboratory parameters, and therapeutic methods of COVID-19 patients in Hunan, China. Setting The First Hospital of Changsha, First People's Hospital of Huaihua, and the Central Hospital of Loudi, Hunan province, China. Methods This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 19 publications
4
52
0
1
Order By: Relevance
“…After review of the titles and abstracts, 63 studies were considered to meet the criteria for full-text scanning. After removal of reviews, duplicate articles with smaller sample size, and studies which did not report liver biochemical parameters, 23 studies met the inclusion criteria [18] , [19] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] . Additionally, two studies were enrolled after review of the reference lists of all included studies and major review and meta-analyses [44] , [45] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After review of the titles and abstracts, 63 studies were considered to meet the criteria for full-text scanning. After removal of reviews, duplicate articles with smaller sample size, and studies which did not report liver biochemical parameters, 23 studies met the inclusion criteria [18] , [19] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] . Additionally, two studies were enrolled after review of the reference lists of all included studies and major review and meta-analyses [44] , [45] .…”
Section: Resultsmentioning
confidence: 99%
“…All these studies were published in 2020 and could be divided into non-survivors group and survivors group. Among them, 23 studies were from China [18] , [19] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [45] , one from the United States [35] and one from Spain [44] . Among the 23 studies from China, 20 studies were written in English and three in Chinese [18] , [28] , [42] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological researches found SARS-CoV-2 could potently bind with angiotensin converting enzyme 2 (ACE2), a receptor abundantly expressed in a variety of human organ cells [22], which might account for multiple adverse effects in COVID-19 patients, such as lung, nervous system, kidney, liver, gastrointestinal system and heart [23][24][25][26]. There are no validated effective therapeutic approaches for COVID-19 patients, and the main treatment interventions are supportive therapy, including oxygen therapy, antiviral medications, antibiotics, corticosteroids and traditional Chinese medications [27]. The e cacy of antiviral medications that have been used for SARS and MERS is needed further explore in COVID-19 patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Different features of CT imaging had been reported in the included studies. However, the frequently reported features were ground glass opacity (GGO), reported in 15 studies (1-6, 8, 10-18), consolidation, reported in 10 studies(1,3,5,6,10,11,(14)(15)(16)(17), linear opacity, reported in 4 studies(1,3,6,16), bronchial wall thickening, reported in 3 studies(5,6,14), and bilateral lung involvement, reported in 15 studies(2-6, 8, 11-14, 16-20) (Table 1). Risk of bias was generally low after considering the observational designs (Supplementary…”
mentioning
confidence: 99%